PENINGKATAN HASIL BELAJAR OPERASI HITUNG SATUAN WAKTU DENGAN PENDEKATAN CTL DI KELAS V SD - Umi, Faridatul; Masniladevi, Masniladevi; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of this study was to describe the planning, implementation, and improvement of learning outcomes in the operation of time unit with the application of the Contextual Teaching And Learning approach of students at grade V in SD Negeri 05 Air Tawar Barat Kota Padang. This research was classroom action research with qualitative and quantitative approaches. Subjects of this research were teachers and 34 students. The results showed: a) lesson plan in cycle 1, was 82. 14%, increased to 92,85% in cycle 2. b) teacher activity in cycle 1 was 80,35% increased to 92,85% in cycle 2. c) student activity in cycle 1 was 71,42%  and it increased to 89,28%  in cycle 2. d) student learning outcomes  in cycle 1 was  77.70  increased to 88,08 in cycle 2. It could be concluded that Contextual Teaching And Learning can improve student learning outcomes on operation of time unit at grade 5 of elementary school student. Keywords: time unit, CTL, learning outcomes.